Methylene blue removal using zinc and magnesium oxides doped banana peels: Isotherm, kinetics and mechanism - Pornsawai Praipipat; Pimploy Ngamsurach; Kanokwan Bunchu; Varunya Lekwaree (Environmental Chemistry and Ecotoxicology)
Three banana peel materials which were banana-doped ZnO beads (BZB), banana-doped MgO beads (BMB), and banana-doped ZnO + MgO beads (BZMB) for adsorbing methylene blue dye (MB) were synthesized and characterized by several techniques of XRD, FTIR, FESEM-FIB, EDX, BET, and pHpzc. Batch experiments, material reusability experiments, adsorption patterns and mechanisms, and thermodynamic studies were examined their abilities for adsorbing MB. The specific ZnO or MgO peaks and chemical functional groups of ZnO, and MgO were detected in all materials by XRD and FTIR analysis. They had a spherical shape with heterogeneous surfaces, and the specific characteristic structure of ZnO or MgO and the elements of zinc and magnesium were found by FESEM-FIB and EDX analysis. The behaviors of N2 adsorption-desorption isotherm of all materials were type I with H4 hysteresis loop indicating microporous materials. The pHpzc values of BZB, BMB, and BZMB were 5.93, 9.61, and 8.95. BZMB demonstrated a higher MB removal efficiency at 98.68 % than BZB and BMB, so the additions of both ZnO and MgO increased MB removal efficiency more than the addition of only ZnO or MgO. Moreover, they could be reused in more than six adsorption cycles with high removal efficiencies of more than 54 %. Freundlich and pseudo-second-order kinetic models were best-fit models for all materials corresponding to a chemisorption process. They were exothermic processes that did not favor MB adsorptions with increasing temperature.